2011
DOI: 10.4061/2011/936794
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Proliferative Dermatitis in Mice: NFκB Activation Autoinflammatory Disease

Abstract: Autoinflammatory diseases are a heterogeneous group of congenital diseases characterized by the presence of recurrent inflammation, in the absence of infectious agents, detectable autoantibodies or antigen-specific autoreactive T-cells. SHARPIN deficient mice presents multiorgan chronic inflammation without known autoantibodies or autoreactive T-cells, designated Sharpincpdm. Histological studies demonstrated epidermal hyperproliferation, Th-2 inflammation, and keratinocyte apoptosis in this mutant. The mutant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
0
8
1
Order By: Relevance
“…IFN-g-mediated increase of HOIP and HOIL-1L-protected cpdm cells from TNF-a-mediated apoptosis both in vitro and in vivo cpdm mice are spontaneous mutant mice lacking SHARPIN (15,29). As observed in the WT cells, IFN-g increased the expression of HOIP and HOIL-1L mRNA in MEFs from cpdm mice ( Fig.…”
Section: Ifn-g Augments Nf-kb Activation By Increasing the Amount Of mentioning
confidence: 74%
See 2 more Smart Citations
“…IFN-g-mediated increase of HOIP and HOIL-1L-protected cpdm cells from TNF-a-mediated apoptosis both in vitro and in vivo cpdm mice are spontaneous mutant mice lacking SHARPIN (15,29). As observed in the WT cells, IFN-g increased the expression of HOIP and HOIL-1L mRNA in MEFs from cpdm mice ( Fig.…”
Section: Ifn-g Augments Nf-kb Activation By Increasing the Amount Of mentioning
confidence: 74%
“…Although the precise mechanism underscoring chronic dermatitis in cpdm mice has not been clarified yet, both TNF-a and increased keratinocyte apoptosis have been suggested to be involved in the pathogenesis of dermatitis (16,29). Because we observed that IFN-g protects cpdm keratinocytes from TNF-a-induced apoptosis and activates NF-kB both in vitro and in vivo, we injected IFN-g once a day into the back of cpdm mice for 3 wk to evaluate the effect of IFN-g on the severity of cpdm dermatitis.…”
Section: Amelioration Of Dermatitis By Sc Injection Of Ifn-g In Cpdmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic inflammation in Sharpin cpdm/cpdm mice is characterized by enhanced infiltration of immune cells to many tissues including the skin [ 1 , 29 ], as well as increased numbers of white blood cells in the peripheral blood [ 30 ]. Interestingly, leukocyte (CD45 + ; Fig 3A and 3B ), macrophage (F4/80 + ; Fig 3C and 3D ) and mast cell (Toluidine blue + ; Fig 3E and 3F ) infiltration into the dermis of Sharpin cpdm/cpdm mice was not affected by the Itgb1 function-blocking antibody, indicating that inflammation was not reduced.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, SIPL1 is involved in the inside-out activation of β1-integrin through direct binding to the α-integrin subunit (19). Loss of SIPL1 expression is also a causative factor of the chronic proliferative dermatitis (CPDM) phenotype in mice as a result of abnormal activation of NF-κB (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%